Effect of Dapagliflozin on Urine Metabolome in Patients with Type 2 Diabetes - Bletsa, Evdoxia (J Clin Endocrinol Metab, 2021)
CONTEXT: Inhibitors of sodium-glucose cotransporters-2 have cardio- and renoprotective properties. However, the underlying mechanisms remain indeterminate. OBJECTIVE: To evaluate the effect of dapagliflozin on renal metabolism assessed by urine metabolome analysis in patients with type 2 diabetes. DESIGN: Prospective cohort study. SETTING: Outpatient diabetes clinic of a tertiary academic center. PATIENTS: Eighty patients with hemoglobin A1c > 7% on metformin monotherapy were prospectively enrolled. INTERVENTION: Fifty patients were treated with dapagliflozin for 3 months. To exclude that the changes observed in urine metabolome were merely the result of the improvement in glycemia, 30 patients treated with insulin degludec were used for comparison. MAIN OUTCOME MEASURE: Changes in urine metabolic profile before and after the administration of dapagliflozin and insulin degludec were assessed by proton-nuclear magnetic resonance spectroscopy. RESULTS: In multivariate analysis urine metabolome was significantly altered by dapagliflozin (R(2)X = 0.819, R(2)Y = 0.627, Q(2)Y = 0.362, and coefficient of variation analysis of variance, P < 0.001) but not insulin. After dapagliflozin, the urine concentrations of ketone bodies, lactate, branched chain amino acids (P < 0.001), betaine, myo-inositol (P < 0001), and N-methylhydantoin (P < 0.005) were significantly increased. Additionally, the urine levels of alanine, creatine, sarcosine, and citrate were also increased (P < 0001, P <0.0001, and P <0.0005, respectively) whereas anserine decreased (P < 0005). CONCLUSIONS: Dapagliflozin significantly affects urine metabolome in patients with type 2 diabetes in a glucose lowering-independent way. Most of the observed changes can be considered beneficial and may contribute to the renoprotective properties of dapagliflozin.